Improving English Learning Outcomes Using the Scramble Learning Method for Class VII Students of MTs Daarul Uluum PUI Ranji - Rully Khoeru Solihin; Muaz Muaz (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
To be successful, students must participate actively in the learning process. A scramble, for example, is a method in which each student is extremely active because they are held accountable for the success of their group. One of the learning methods that can be used to help students learn English better is the scramble method. The purpose of this study is to explain how the Scramble learning method improved English learning outcomes for students in the seventh grade at MTs Daarul Uluum PUI Ranji. In this study, Classroom Action Research (CAR) was used in two cycles. Each cycle is divided into four stages: planning, implementation, observation, and reflection. Cycle I. Planning was based on preliminary observations. Cycle II planning is based on the results of Cycle I reflection. According to the study's findings, using the scramble method to solve the problem of learning English resulted in an increase in student learning outcomes from cycle I to cycle II. Learning outcomes in the first cycle averaged 76,25, or 75% completeness, and increased significantly to 81.71, or 84% completeness, in the second cycle. This has increased by 9%. As a result, it can be concluded that using the scramble method can improve the English learning outcomes of class VII students at MTs Daarul Uluum PUI Ranji.